Análisis histórico de los determinantes del precio internacional del petróleo a partir de mediados del siglo XX (2017)
Throughout this document, the aim is to study the history of the oil industry since the beginning of the 20th century, with special emphasis on the fluctuation and the most critical stages for the price of a barrel, which began in the middle of the 20th century in the 1990s. 50. In addition, make a theoretical approach about the determinants that dictate the international price of oil. And finally, carry out an analysis around the international political interference towards the consolidation of the price of oil.